IMPLEMENTATION OF HYBRID ONLINE LEARNING WITH WHATSAPP NOTIFICATION FEATURES USING THE SCRUM METHOD AT SMA ANGKASA 1 MEDAN - Mahendra, Tarisa Aulia; Elhanafi, Andi Marwan (Cattleya Darmaya Fortuna, 2025)
In education, scheduling is crucial and can impact the effectiveness of the learning process. This study aims to create an automated e-learning-based scheduling system equipped with a WhatsApp notification feature. The system was developed using the Scrum method, known for its iterative and incremental project management approach. The system aims to provide students and teachers with easy access to class schedules and direct notifications. Implementing this system at SMA Angkasa 1 Medan is expected to improve efficiency and effectiveness in the educational process. The findings of the study indicate that the system is able to reduce scheduling errors and increase student participation through accurate reminders. Furthermore, the study also identifies various challenges that emerged during the development process and the steps taken to address these issues. Therefore, this automated scheduling system is expected to make a positive contribution to educational institutions in today's digital era